2022
DOI: 10.1038/s41598-022-04808-9
|View full text |Cite
|
Sign up to set email alerts
|

Specific gut bacterial responses to natural diets of tropical birds

Abstract: The composition of gut bacterial communities is strongly influenced by the host diet in many animal taxa. For birds, the effect of diet on the microbiomes has been documented through diet manipulation studies. However, for wild birds, most studies have drawn on literature-based information to decipher the dietary effects, thereby, overlooking individual variation in dietary intake. Here we examine how naturally consumed diets influence the composition of the crop and cloacal microbiomes of twenty-one tropical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 57 publications
4
46
0
Order By: Relevance
“…Therefore, it is difficult to disentangle the individual effects of environmental and genetic factors on the gut microbiota. Several studies have identified dietary factors influencing the gut microbiota; however, in these studies, there were significant differences in dietary composition among the individuals within the same species ( Bodawatta et al, 2022b ), and broad dietary classifications (e.g., herbivorous, carnivorous, and omnivorous) were more significant than the variations in diet ( Hird et al, 2015 ). In the winter, farmland-dependent birds have to become herbivory, and thus, our study species share the same dietary factors.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult to disentangle the individual effects of environmental and genetic factors on the gut microbiota. Several studies have identified dietary factors influencing the gut microbiota; however, in these studies, there were significant differences in dietary composition among the individuals within the same species ( Bodawatta et al, 2022b ), and broad dietary classifications (e.g., herbivorous, carnivorous, and omnivorous) were more significant than the variations in diet ( Hird et al, 2015 ). In the winter, farmland-dependent birds have to become herbivory, and thus, our study species share the same dietary factors.…”
Section: Discussionmentioning
confidence: 99%
“…Both species are dimorphic and monogamous, with females building the nest, and laying and incubating the eggs, while both parents feed the brood [42, 44, 45]. BTs and GTs differ in body size [42] and therefore prey selection [46, 47], which is expected to affect gut microbiomes [23, 48].…”
Section: Methodsmentioning
confidence: 99%
“…BTs and GTs differ in body size [42] and therefore prey selection [46,47], which is expected to affect gut microbiomes [23,48].…”
Section: Study Speciesmentioning
confidence: 99%
“…Such peculiarity may have arisen due to adaptations of avian digestive system to flight, constraining relative size of individual internals (Bodawatta et al, 2021). Specifically, caeca and other parts of the digestive system are typically reduced in passerines, resulting in lesser potential for physiologically significant and stable host–microbiota interactions (Bodawatta et al, 2022; Caviedes‐Vidal et al, 2007). Major differences between GM of mammals and birds are found also in representation of major bacterial phyla.…”
Section: Introductionmentioning
confidence: 99%